Tenuibiotus, a new genus of Macrobiotidae (Eutardigrada) - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2011)
The group of Macrobiotus species having claws of the tenuis-type is discussed and a new genus, named Tenuibiotus, is instituted. The tenuis-type claws are characterised by the fusion of the primary and secondary branches over a long distance so that the common tract is longer than that found in other members of the Macrobiotidae. Distally, the secondary branch is clearly shorter than the primary branch, and forms with it almost a right angle. In all the known species attributable to the new genus, the buccal tube is narrow, the buccal cavity is small with small peribuccal lamellae; the eggs are laid freely and have conical or trunco-conical processes.